2018
DOI: 10.4236/health.2018.1011118
|View full text |Cite
|
Sign up to set email alerts
|

Italian Psychometric Validation of the Multidimensional Students’ Health-Promoting Lifestyle Profile Scale

Abstract: The present study examines the factorial structure and assesses the psychometric properties of the adapted multidimensional Health-Promoting Lifestyle Profile II Scale, considering a sample of Italian university students who participated to an online survey. The original 52-items Scale showed a high overall internal consistency. Four of the six subscales were associated with good values of the Cronbach's α coefficient, whereas two subscales had lower values. Hence corrected item-total correlation was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Furthermore, the discriminant validity of the factors in HPLP-II-M was found to be satisfactory, indicating that the latent variables in the CFA measurement model of HPLP-II-M contribute information which is not captured by the other latent variables. [22]. The present study retained 50 items in the final measurement model, after removal of two low factor loading items.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, the discriminant validity of the factors in HPLP-II-M was found to be satisfactory, indicating that the latent variables in the CFA measurement model of HPLP-II-M contribute information which is not captured by the other latent variables. [22]. The present study retained 50 items in the final measurement model, after removal of two low factor loading items.…”
Section: Discussionmentioning
confidence: 96%
“…Item Q1 was removed in the Chinese validation study during EFA stage [17], and item Q50 was removed in the Spanish study due to very low corrected item-total correlation value < 0.20 [18]. Item Q50 was also removed in the Italian study due to its contribution to low reliability of the scale [22] and Chinese validation study due to its insignificant factor loadings in a CFA analysis [16]. Removal of these items improved the fit of the model in those studies as well as in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous validation studies of HPLP-II reported varying total number of items that fit the CFA measurement model. For example, based on psychometric properties, Pérez-Fortis et al [52] retained 44 items for Spanish version, Meihan et al [36] retained 30 items and 51 items respectively for the Chinese version, while Savarese et al [53] retained 26 items for the Italian version of the HPLP-II. A study by Kuan, Kue, Abdullah, and Tai [50] in Malaysia retained 50 items in the final measurement model, after removal of two low factor loading items.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of lifestyle leads to satisfaction, success at work, and physical health, called the health-promoting lifestyle profile (HPLP). It consists of six dimensions as follows: physical activity, nutrition, health responsibility, spiritual growth, interpersonal relations, and stress management [ 2 , 7 , 8 ]. Students often neglect to maintain a healthy lifestyle, which puts them at risk of old age diseases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%